ENHANCING LEARNER AUTONOMY AND INTERCULTURAL COMPETENCE THROUGH VIRTUAL EXCHANGE IN ESL CLASSROOMS - Abdullah, Amelia; Saad , Sharina; Zolkifli, Alia Nabella Fateha (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
In today’s globalized learning environment, English as a Second Language (ESL) education must go beyond linguistic competence to foster autonomy and intercultural awareness. This study investigates the effects of structured virtual exchange programs on Malaysian tertiary ESL students’ learner autonomy and intercultural competence. Forty students engaged in six weeks of collaborative online projects with peers from an international partner university. A convergent mixed-methods design was employed, incorporating pre- and post-intervention surveys and semi-structured interviews. Quantitative results revealed significant gains in self-directed learning behaviors, goal-setting, and intercultural adaptability. Qualitative findings highlighted learners’ increased motivation, cultural empathy, and resilience in managing logistical challenges. These results indicate that virtual exchange can function as a dual catalyst for autonomy and intercultural competence, aligning with Malaysia’s educational goals and the United Nations Sustainable Development Goal 4. The study concludes that embedding structured intercultural digital collaboration into ESL curricula can enhance learner-centered pedagogies and prepare students for global citizenship.